Position of Islamic Jurisprudence about Contradicting Medical Scientific Fundamentals: - Boufaghes, Saida Messaoud; Zeghad, Seiflislam Mohammed (Journal of Islamic Sciences, 2022)
The study aims to understand the reality of medical scientific fundamentals and their legal dimension, using the inductive-analytical method monitoring the opinion of Islamic Jurisprudence by clarifying where a Muslim physician is judged to be in contradiction with these fundamentals. This study is important since it reinforces the idea of ​​cognitive integration between Islamic sciences and other disciplines, and presents a scientific-intellectual approach to clarify the foundations of the Islamic method in guiding medical work to achieve human happiness. The study showed that the approval of scientific medical principles is conditional on the occurrence of medical work in accordance with its purposes, and foregoing the responsibility of the Muslim physician in Islamic jurisprudence.